KEJADIAN ANKILOSTOMIASIS PADA KUCING DI YOGYAKARTA DILIHAT BERDASARKAN JENIS KELAMIN - , FATKHURAHMAN ARIFIN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ancylostomiasis was one worm-caused infection case frequently infecting cats. For that conducted research on Ancylostomiasis in cats in Yogyakarta on the terms of the sexes. The purpose of this research was to determine the incidence rate Ancylostomiasis in Yogyakarta on female and male cats. There were 280 faecal samples exploited in this research which came from various place in DI Yogyakarta. Then, faecal samples were grouped by rearing pattern that were well reared in houses, semi-feral, dan feral. The owner also filled questionnaire those contained generality of cat, sex, age, breed, vaccination status, parentage of cat, and rearing system. The Toxocarasp.worm eggs were identified by using native and centrifugal methods